PENGARUH PERATURAN PERPAJAKAN DAN TARIF PAJAK PROGRESIF TERHADAP PENERIMAAN PAJAK DI SAMSAT KELAPA DUA KABUPATEN TANGERANG - Ambarwati; Salza Febriyani (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Tax regulations serve as the legal foundation governing tax obligations and collection mechanisms, while progressive tax rates reflect fiscal fairness by imposing higher rates as the number or value of vehicles increases. This system plays a crucial part in promoting taxpayer compliance and optimizing local revenue. This study aimed to analyze the impact of tax regulations and progressive tax rates on Motor Vehicle Tax (PKB) revenue at the Kelapa Dua Samsat Office in Tangerang Regency. This study used a quantitative approach, by employing survey methods and multiple linear regression analysis. The results of validity and reliability tests indicated that the research instruments are valid and reliable. Partial tests (t-tests) prove that both tax regulations and progressive tax rates have a positive and significant impact on PKB revenue. Simultaneous tests (F-tests) reinforce that both independent variables together have a significant impact on the dependent variable. The coefficient of determination (R²) value of 0.403 indicated that 40.3% of the variation in PKB revenue can be explained by tax regulations and progressive tax rates. These findings support the Slippery Slope Framework and Fiscal Exchange Theory, which emphasize the importance of combining regulatory strength and perceptions of fiscal justice to improve tax compliance. This study has important implications for the formulation of fairer, more transparent, and more effective local tax policies to optimize motor vehicle tax revenue.